On pins and needles: How vaccines are portrayed on Pinterest. Issue 39 (22nd September 2015) - Guidry, Jeanine P.D.; Carlyle, Kellie; Messner, Marcus; Jin, Yan
Highlights This study analyzed 800 vaccine-related Pinterest posts. The majority of the pins were anti-vaccine. Concerns about vaccine safety and side effects were oft-repeated themes. Perceived barriers appeared in more than half of the pins.